Quraish Shihab's Interpretation of Gender Equality In Tafsir Al-Misbah - Moh. Nor Ichwan; Faizal Amin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This study explores Quraish Shihab's interpretation of gender equality issues, such as equality in creation, marriage, prophethood, the role of women in the public world, and others. This research uses the library research method, and the first and primary source is Tafsir al-Misbah. Operationally, the researchers readvarious literature written by scholars, both East and West, on the concept of gender from the perspective of feminism. Then, the researchers read the Tafsir al-Misbah on the same theme. Does feminist thought influence Quraish Shihab's interpretation or not? This research finds that according to Quraish Shihab, the issue of gender equality in the Qur'an must be understood proportionally, unlike gender practitioners who interpret the Qur'an excessively and seem to impose their will. Quraish Shihab argues that men and women are naturally different both physically and psychologically. Both also have equality in terms of humanity and rights. Women have advantages that men do not have and vice versa. Both need each other.Kajian ini mengeksplorasi interpretasi Quraish Shihab terhadap isu-isu kesetaraan gender, seperti kesetaraan dalam penciptaan, perkawinan, kenabian, peran perempuan di dunia publik, dan lain-lain. Penelitian ini menggunakan metode penelitian kepustakaan, dan sumber pertama dan utama adalah Tafsir al-Misbah. Secara operasional, peneliti membaca berbagai literatur yang ditulis oleh para sarjana, baik Timur maupun Barat, tentang konsep gender dari perspektif feminisme. Kemudian peneliti membacakan Tafsir al-Misbah dengan tema yang sama. Apakah pemikiran feminis mempengaruhi penafsiran Quraish Shihab atau tidak? Penelitian ini menemukan bahwa menurut Quraish Shihab, persoalan kesetaraan gender dalam Al-Qur'an harus dipahami secara proporsional, tidak seperti praktisi gender yang menafsirkan Al-Qur'an secara berlebihan dan terkesan memaksakan kehendaknya. Quraish Shihab berpendapat bahwa laki-laki dan perempuan secara alamiah berbeda baik secara fisik maupun psikis. Keduanya juga memiliki kesetaraan dalam hal kemanusiaan dan hak. Wanita memiliki kelebihan yang tidak dimiliki pria dan sebaliknya. Keduanya saling membutuhkan.